First follow‐up of a breakable stent for implantation in infants dedicated for a life‐long stay. Issue 6 (22nd February 2018) - Zartner, Peter A.; Neudorf, Ulrich; Bierbach, Benjamin; Hart, Chris; Schneider, Martin B.
Abstract: Objective and methods: The use of conventional metal stents in infants is severely limited by subsequent somatic growth. The use of a breakable balloon expandable stent (BS) designed for initial implant at small diameters but with properties that allow unlimited dilation in line with growth has potential advantages in this patient group. This study reports our experience with this stent between 2010 and 2014. A total of 17 BS were implanted in 14 infants (mean age 4.8 months). All but one stent was placed into the aorta to treat coarctation. Results: All implantations were successful and initial gradients dropped from a mean of 25–6 mm Hg (range from 1–50 down to 0–24 mm Hg). Mean follow‐up was 3.3 years (range 5 days to 7 years) with a total cumulative follow‐up of 46.7 patient years. Stent redilation was performed a median of 2.5 times (range 0–5). Sixteen stents in 13 patients remain in place. Following redilation beyond 10 mm, circumferential integrity of the BS was lost in 10 patients. No further stent implantation or related surgery was necessary. A 3 mm dissection occurred in one patient after redilation. Conclusions: The BS performed well in terms of relief of stenosis and could be successfully dilated during the phase of the infants' most rapid growth. Mild intimal proliferation occurred in some patients early after implantation. In the course of the stepwise redilations and growth adjustments, both, planned longitudinal and transverse fractures occurred without allowing a collapse of the stented area.